Mind and Cosmos: Why the Neo-Darwinian Conception of Nature Is Almost Certainly False by Thomas Nagel - McDaniel, Stan V. (Journal of Scientific Exploration, 2013)
The subtitle of this surprisingly brief volume by Thomas Nagel presages something more, and something less, than what at a glance it may seem to promise. In such a confined space as a mere 128 pages, coming from such a noted philosopher, one might expect that Nagel has consolidated and refined a highly focused, decisive argument against the prevalent materialist–reductionist account of mind and its place in nature. Those of a materialist view will not likely be concerned, since philosophical objections seldom seem to have much effect on that paradigm. On the other hand, those who feel deeply that something is amiss in the reductionist account might be a bit disturbed when they realize the import of the word almost in the subtitle. Is Nagel hedging his bets? That puzzling “almost” is easier to understand, however, when we reach the concluding summary, which might better have been placed right up front on page 1: "Philosophy has to proceed comparatively. The best we can do is to develop the rival alternative conceptions in each important domain as fully and carefully as possible, depending on our antecedent sympathies, and see how they measure up. That is a more credible form of progress than decisive proof or refutation." (p. 127)